PENGARUH PENGAWASAN PIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI KANTOR DESA CARAWALI KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG - Muhammad Yusuf; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The purpose of this study was to determine the effect of leadership oversight on employee work discipline in the office of Carawali Village, Watang Pulu Subdistrict, Sidenreng Rappang Regency and the factors that influenced the supervisory supervision of employee work discipline at the Carawali Village office in Watang Pulu District, Sidenreng Rappang District. The population in this study were 54 people. Calculation of samples using saturated sampling, that is, taking all the population as a sample is as many as 54 people. This type of research is quantitative descriptive. The results of this study are the leadership supervision of employee work discipline in the Carawali Village office in Watang Pulu District, Sidenreng Rappang District, which has no significant effect of seeing the processed data in the ANOVA table, it turns out that the t value is ≤ t table or 1.11 ≤ 2.00 and significance level 0.27 (F> 0.05) then Ho is accepted and Ha is rejected, meaning that leadership supervision (X) does not have a significant effect on employee work discipline (Y). The factors that influence supervision are seen from the first factor which has an influence of 22.5%. The second factor has an influence of 15.4%. The third factor has an influence of 38.2% and the fourth factor has an influence of 20.3%. Keywords:supervision and work discipline